A Critical Study of The Implementation of Innovations For Higher Education - Revati Ramrao Rautrao; Chandrakant Hake (PT FORMOSA CENDEKIA GLOBAL, 2022)
The educationalists are trying to accelerate the pace of development in higher education in order to make it suit the changed circumstances of the country since independence. The question of higher education has become a controversial issue in the present day. The universities are multiplied in number, their academic standards are not improving. In the contrary, they are becoming targets for public criticism as their standards are lagging. The innovations that were floated in the field of higher education have been implemented by only a few. The aim of innovation is the change for the better. Change brings progress. The present investigator is proposing to study the implementation of some innovations in higher education. The curriculum should be designed to promote Entrepreneurship and Governance & foster Entrepreneurship in the Education Sector. The level of education, in turn, sets the extent of prosperity that may enrich aggressiveness. The competitiveness level additionally determines the rates of modification in academic structure obtained by academic policies, that successively are the elemental drivers of it's growth rates.